A 2020 Update on 20/20 X 2: Diplopia after Inadvertent Strabismus Surgery Complications. Issue 4 (2nd October 2021) - Winter, Aaron W.; Granet, David B.
ABSTRACT: The goals of successful strabismus surgery include the optimization of binocular potential through the establishment, reestablishment, or improvement of ocular alignment leading to a reduction or resolution of diplopia, as well as an improvement of compensatory head position or cosmesis. Fortunately, the incidence of new postoperative diplopia in patients without diplopia prior to strabismus surgery is extremely uncommon (less than 2%). Alternatively in a patient with preoperative diplopia that persists postoperatively, it is important to establish whether the diplopia is unchanged, increased, or of the same magnitude but shifted to a more disruptive position of gaze. During preoperative planning, the surgeon tries to anticipate and thus avoid postoperative diplopia. If the postoperative diplopia is unexpected, then a dispassionate evaluation of the outcome to identify planning, mechanical, or other factors is necessitated. These factors will be explored below systematically in the preoperative, intraoperative, and postoperative phases.